Penetration of private places in Theodotian Susanna - Pierre J. Jordaan; Chihwei Chang (HTS Teologiese Studies/Theological Studies, 2018)
The Theodotian Susanna has been studied by various scholars in various ways. Each attempt to give some meaning to this narrative has a different emphasis from a text, context or receiver based angle. This paper presents a mixture of text and context based angles. It focuses on the different spaces in Theodotian Susanna, that is, the house, garden, court and finally heaven. Each of these spaces is contested, but there can only be one victor.